The spiritual VS physical certainties (اليقين): inspirations from al-Ghazali`s intellectual heritage - Shogar, Ibrahim (2017)
According to al-Ghazali, there are four different forms of knowledge: 1.Educated knowledge ( تقليدي ): knowledge that attained through education by others, training, or by reporting; 2.Common-sense knowledge (حسي ): the knowledge that attained through sense perceptions (this type can be defined as counterpart of scientific knowledge that acquired through carful observation and experiment, as explained by contemporary philosophers, such as John Dewey and C. D. Broad); 3.Demonstrative knowledge (نظري): the inferred knowledge that acquired through inductive and deductive reasoning, or based on analogy; 4.A Priori knowledge (ضروري ): the innate and self-evidence knowledge that based on principles of reason ( الأول اٌت ), such as to know that ten is more than three, and knowing that the same thing cannot be dead and life at the same time.